213 - ECT-AD: Ethics and informed consent issues. (October 2021) - Nykamp, Louis; Forester, Brent P.; Hermida, Adriana P.; Mueller, Martina; Petrides, Georgios; Heintz, Hannah; Lapid, Maria I.
Abstract: Agitation is experienced by over 90% of individuals with Alzheimer's disease (AD) which increases morbidity and mortality and contribute to caregiver burden. There are no FDA-approved treatments for severe agitation in people with advanced dementia. Behavioral interventions are first-line management strategies but are not effective in the most severely agitated patients. Off-label use of psychotropic medications have limited efficacy and risk for adverse effects. New management strategies for severe agitation in AD refractory to psychopharmacologic and behavioral interventions are timely and warranted. Preliminary studies provide evidence for the safety and efficacy of acute electroconvulsive therapy (ECT) in reducing agitation in this population. The ECT-AD study is a multi-site NIH-funded randomized single-blind randomized controlled trial to investigate the safety and efficacy of ECT in severe and treatment refractory agitation and aggression in AD. In a vulnerable population with advanced dementia and lack of capacity to provide informed consent, there are ethical and consent issues that need to be considered. In this presentation, we will describe the human research subject aspects of working with this population, the process of informed consent and variation of state laws, and efforts to ensure participant safety and minimize undue influence or coercion.